Popular culture and the ’darker side’ of alternative spirituality: the case of metal music - Moberg, Marcus (Scripta Instituti Donneriani Aboensis, 2009)
Metal is perhaps the most extreme and aggressive form of contemporary Western popular music. Even though it continues to spark controversy and debate, it has also enjoyed enduring popularity for decades and has spread on a global scale. Metal music and culture has always been characterized by its fascination for dark and austere themes and imagery. Commonly dealing with topics such as evil, death, war, alienation and suffering, metal groups have traditionally found much inspiration in the world of religion, particularly Judeo-Christian eschatology and apocalypticism, different forms of paganism, occultism, esotericism and, last but not least, Satanism. These kinds of religious/spiritual themes have arguably developed into an integral part of metal culture on the whole. They contribute significantly to investing metal music and culture with an apparent aura of sincerity and mystique as well as to raising its shock and entertainment value. At the same time, metal culture is also marked by its high degree of humour and self-irony, its fondness for exaggeration, spectacle and over-the-top theatrics. Even so, metal stands out as a global popular music culture replete with various kinds of often dark and austere religious and spiritual themes, many of which stand in stark contrast to Christianity. Seen in the wider context of the changing face of religion in the West and the increasingly important role played by popular culture in the transformation of religious and spiritual identities, metal has come to play an important role in the dissemination of a wide variety of ‘dark’ alternative religious/spiritual beliefs and ideas. This article sheds further light on this issue through focusing on some contemporary and successful metal groups from the Nordic countries. In relation to this, attention is also drawn to some of the ways in which dark alternative religious/spiritual ideas may be viewed as having become an inseparable part of some sections of metal culture as they have become actively and consciously explored, and sometimes explicitly promoted, by the well known contemporary metal groups discussed in this article.